Dissertation as a source for prosopography of scientific communities - Railiene, Birute; Mikniene, Giedre (Circumscribere International Journal for the History of Science, 2016)
This article deals with the bibliometric approach to the metadata of a dissertation record in a catalogue or database. As a document, a dissertation provides data on new knowledge, but also encodes important scientometric information. Research advising is one of main scholarly communication formal links (besides co-authorship and citation) in a social structure of science. PhD records may expose a scientific relation of research-advising both at the personal and institutional levels within a certain scientific area. This survey was inspired by bibliographical indexes of dissertation output in certain fields and during certain periods: 1793 to 1842, 1940 to 1993 in one country – Lithuania. The survey of selected scientific communities from 1945 to 1990 in Lithuania reveals a vast retrospective of scholarly communication, however, it is fragmented and not satisfactory for a comprehensive prosopographic mapping of scholarly communities within a science field or a country. After reviewing a tradition and style of electronic theses and dissertations (ETD) cataloguing and metadata creation, obstacles for prosopographic surveys and data mining in catalogues and databases of ETDs are revealed.